2013
DOI: 10.1128/jvi.01327-13
|View full text |Cite
|
Sign up to set email alerts
|

The Avian XPR1 Gammaretrovirus Receptor Is under Positive Selection and Is Disabled in Bird Species in Contact with Virus-Infected Wild Mice

Abstract: Xenotropic mouse leukemia viruses (X-MLVs) are broadly infectious for mammals except most of the classical strains of laboratory mice. These gammaretroviruses rely on the XPR1 receptor for entry, and the unique resistance of laboratory mice is due to two mutations in different putative XPR1 extracellular loops. Cells from avian species differ in susceptibility to X-MLVs, and 2 replacement mutations in the virus-resistant chicken XPR1 (K496Q and Q579E) distinguish it from the more permissive duck and quail rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 68 publications
2
21
0
Order By: Relevance
“…Also, proteins like MAP4 that are involved in intracellular trafficking have also been shown to be a common target of viral hijacking (Radtke et al, 2006). We conclude that positive selection can shape the evolution of host factor genes, consistent with other recent studies on cell surface receptors (Demogines et al, 2013; Kaelber et al, 2012; Martin et al, 2013), components of the nuclear pore (Schaller et al, 2011), and DNA repair machinery (Demogines et al, 2010; Sawyer & Malik, 2006). …”
Section: Discussionsupporting
confidence: 91%
“…Also, proteins like MAP4 that are involved in intracellular trafficking have also been shown to be a common target of viral hijacking (Radtke et al, 2006). We conclude that positive selection can shape the evolution of host factor genes, consistent with other recent studies on cell surface receptors (Demogines et al, 2013; Kaelber et al, 2012; Martin et al, 2013), components of the nuclear pore (Schaller et al, 2011), and DNA repair machinery (Demogines et al, 2010; Sawyer & Malik, 2006). …”
Section: Discussionsupporting
confidence: 91%
“…Host restriction factors have been shown to play a key role in host defense, as have mutations in the cell surface receptors required for retroviral infection (2). Of direct relevance here is a recent study that found that birds with a high risk of exposure to mice harboring an infective gammaretrovirus (ground-dwelling fowl and raptor species) have evolved receptordisabling mutations, suggestive of a defensive role (30). Examination of ERV distribution patterns among host taxa provides opportunities to frame further investigations into the evolution of host genetic factors against retroviruses.…”
Section: Discussionmentioning
confidence: 88%
“…Most mammals are susceptible to XP-MLVs, and K500 is completely invariant in the mammals we examined previously with the single exception of the X-MLV-restrictive laboratory mouse which carries E500 (Figure 1A) (Yan et al, 2010). In the avian lineage, the homologous site, K496, is also critical for XPR1 receptor function, and avian XPR1 receptor function can be disabled by two naturally occurring mutations at this site, K496E and K496Q (Martin et al, 2013). The mouse mutation and both bird mutations all result from substitutions in the first position of this codon (CAA and GAA).…”
Section: Resultsmentioning
confidence: 99%